(3GdhLjR aj eHGOF GdbGfhf (B:s (3GdfXQjI GdYGeI ddbGfhf(B-(3GdfXQjI GdYGeI ddMb(B-(3GdfXQjI GdYGeI ddEdJRGe(B-(3CSGSjGJ GdbGfhf GdJLGQj (B/s - (3Ydj MSf, ShRGfs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2001)
(3GdfXQjI GdYGeI ddbGfhf,GdfXQjI GdYGeI ddMb,GdfXQjI GdYGeI ddEdJRGeGJ,eHGOF GdbGfhf GdJLGQjs
Keywords: (3GdbGfhfs; (3GdbGfhf GdJLGQjs